Fetal and neonatal alloimmune thrombocytopenia: predictive factors of intracranial hemorrhage. Issue 1 (7th September 2015) - Delbos, Florent; Bertrand, Gérald; Croisille, Laure; Ansart‐Pirenne, Hélène; Bierling, Philippe; Kaplan, Cécile
Abstract : BACKGROUND: In Caucasians, fetal/neonatal alloimmune thrombocytopenia (FNAIT) is most frequently caused by maternal alloimmunization against the human platelet antigen HPA‐1a. The most serious complication of severe FNAIT is intracranial hemorrhage (ICH). ICH mainly occurs in utero; therefore, there is a need to identify noninvasive predictive factors of ICH to facilitate early identification of this condition and to determine response to maternal therapy. STUDY DESIGN AND METHODS: We studied gynecologic and immunogenetic variables of severe cases of anti‐HPA‐1a FNAIT within three groups: Group I, FNAIT without ICH; Group II, FNAIT with ICH; and Group III, suspected FNAIT cases without detectable maternal anti‐HPA‐1a alloantibodies. RESULTS: ICH was associated with a poor outcome because it led to death in 59% of cases. Multigravida (two or more pregnancies) was overrepresented in Group II, consistent with the high concentrations of maternal HPA‐1a alloantibody and the frequent detection of a strong newborn‐specific HLA class I antibody response at delivery. The proportion of HLA‐DRB4*01:01P (*01:01 or *01:03) women was similar in Groups I and II, but this allele was overrepresented in Group III, in which FNAIT was less severe than in the other two groups. Finally, antenatal intravenous immunoglobulin therapy tended to be more effective in HLA‐DRB3*01:01(+)/HLA‐DRB4*01:01P(+) women than for HLA‐DRB3*01:01(+)/HLA‐DRB4*01:01P(–) women. CONCLUSION: The number of gestations is a predictive factor of ICH in anti‐HPA‐1a–alloimmunized women. Maternal immunogenetic variables should be investigated in the context of maternal immunization and may predict response to maternal therapy in subsequent pregnancies.